Integration of Transcriptome and Methylome Analyses Provides Insight Into the Pathway of Floral Scent Biosynthesis in Prunus mume - Yuan, Xi; Ma, Kaifeng; Zhang, Man; Wang, Jia; Zhang, Qixiang (Frontiers in Genetics, 2021)
DNA methylation is a common epigenetic modification involved in regulating many biological processes. Prunus mume is a famous traditional ornamental and fruit plant, emitted pleasant fragrance, however the epigenetic mechanisms involved in the formation of its floral scent have rarely been reported. By combining whole-genome bisulfite sequencing and RNA-seq, we determined the global change in DNA methylation and expression levels of genes involved in the synthesis of floral scent in four different flowering stages of P. mume. During flowering, the methylation status in the “CHH” sequence context (with H representing A, T, or C) in the promoter regions of genes showed the most significant change. Enrichment analysis showed that the differentially methylated genes (DMGs) are widely involved in eight pathways known to be related to floral scent biosynthesis. As the key biosynthesis pathway of the dominant volatile fragrance of P. mume, the phenylpropane biosynthesis pathway contained the most differentially expressed genes (DEGs) and DMGs. We detected 97 DMGs participated in the most biosynthetic steps of the phenylpropane biosynthesis pathway. Furthermore, among the previously identified genes encoding key enzymes in the biosynthesis of the floral scent of P. mume, 47 candidate genes showed an expression pattern matching the release of floral fragrances, 21 of which were differentially methylated during flowering. Some of these DMGs may or have already been proven to play an important role in biosynthesis of the key floral scent components of P. mume, such as PmCFAT1a/1c, PmBEAT36/37, PmPAL2, PmPAAS3, PmBAR8/9/10, and PmCNL1/3/5/6/14/17/20. In conclusion, our results for the first time revealed that DNA methylation is widely involved in the biosynthesis of floral scent and may play critical roles in regulating the floral scent biosynthesis of P. mume. This study provided insights into floral scent metabolism and can provide a direct reference for molecular breeding.